2018
DOI: 10.1111/fcsr.12254
|View full text |Cite
|
Sign up to set email alerts
|

Training Younger Volunteers to Promote Technology Use Among Older Adults

Abstract: Older adults demonstrate a wide variation in technology skills. Ecological systems theory suggests that technology adoption is the product of process, person, context, and time. Factors that impact the acquisition and transmission of technology skills emerge as a result of processes within and among people and systems. Subjective aging, one factor impacted by ecological systems, is particularly relevant to intergenerational technology training programs. The purpose of this article was to describe the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 13 publications
1
35
0
Order By: Relevance
“…The second category includes studies that often used one-on-one tutoring as the pedagogical approach (e.g., Brown & Strommen, 2018; Lee & Kim, 2018; Tambaum, 2017). The main characteristic of this category and its main difference with the previous one is that the content and the aims of training were based on the participants’ own learning goals (Lee & Kim, 2018), experiences, needs, characteristics, abilities (Patrício & Osório, 2016; Tambaum, 2017), tested level of Internet anxiety (Zhou et al, 2007), or existing habits of using technology and devices (Lee & Kim, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The second category includes studies that often used one-on-one tutoring as the pedagogical approach (e.g., Brown & Strommen, 2018; Lee & Kim, 2018; Tambaum, 2017). The main characteristic of this category and its main difference with the previous one is that the content and the aims of training were based on the participants’ own learning goals (Lee & Kim, 2018), experiences, needs, characteristics, abilities (Patrício & Osório, 2016; Tambaum, 2017), tested level of Internet anxiety (Zhou et al, 2007), or existing habits of using technology and devices (Lee & Kim, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The main characteristic of this category and its main difference with the previous one is that the content and the aims of training were based on the participants’ own learning goals (Lee & Kim, 2018), experiences, needs, characteristics, abilities (Patrício & Osório, 2016; Tambaum, 2017), tested level of Internet anxiety (Zhou et al, 2007), or existing habits of using technology and devices (Lee & Kim, 2018). On the basis of these, the training consisted of individualized lessons (Brown & Strommen, 2018) or short introductory tutorials on how to use an application or device (Nor et al, 2011; Tambaum, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some employees do not see working with computers as their core task and are hesitant to use new systems [ 37 ]. Other studies [ 38 ] have also found that most volunteers are older adults and have a wide variation regarding their technology skills. There was then a need for time and effort to train the volunteers who showed resistance in using the technology, which is in line with what was reported in [ 9 ].…”
Section: Discussionmentioning
confidence: 98%
“…Various media literacy education methods have been applied in supporting older people to use, understand, and create media content and communications. The methods include traditional approaches, such as fixed-length instructor-led courses (e.g., Castilla et al, 2018), learner-centered one-on-one tutoring (e.g., Brown & Strommen, 2018), peer-to-peer teaching (e.g., Sayago, Forbes, & Blat, 2013), intergenerational approaches where significantly younger persons have tutored the seniors (e.g., Gamliel, 2017), and creative pedagogies based on older people's creative content production processes (e.g., Manchester & Facer, 2015). In addition, blended learning and online learning approaches have been used for promoting older people's media literacies (e.g., Manafo & Wong, 2012).…”
Section: Older Peoplementioning
confidence: 99%